ALIH WAHANA SASTRA SEBAGAI STRATEGI LITERASI: REKAYASA KREATIF NOVEL DEWASA MENJADI NOVEL ANAK - Putra Alim, Cahya; Khoiriyah, S. Azimatul; Apsari, Erlyta Audhitia; Zulfikar, Fikri (Universitas Nias Raya, 2025)
The concept of creative engineering of literary vehicle transfer from adult novels to children's novels as a form of adaptation across age segments demands aesthetic and pedagogical sensitivity. This process does not simply transfer the story from one form to another, but is a practice of creative transformation that considers the differences in the horizon of readers' expectations, cognitive capacity, and the needs of children's educational values. This study relies on literary reception theory (Jauss and Iser), Jean Piaget's theory of cognitive development, Linda Hutcheon's theory of literary adaptation, and Graham Wallas' four-stage creativity theory of preparation, incubation, illumination and verification to explain the creative mental process involved in the re-creation of the text. Through this approach, adaptations are made by simplifying the plot and conflict, choosing communicative diction, rejuvenating characters, and reconstructing moral messages to suit child readers. These adjustments still maintain the substance of humanist values contained in adult novels, but are repackaged to be more child-friendly and arouse imagination and empathy. This research shows that creative engineering can be an effective literacy bridge to introduce adult literature to children, while enriching the repertoire of Indonesian children's literature with high-value narratives delivered in a contextual and educational manner.